Process Safety in the Radical Polymerization of Styrene: From Bulk to Solution/Emulsion Process - Owolabi, R. U.; Usman, M. A.; Kehinde, A. J. (Kathmandu University Journal of Science, Engineering and Technology, 2015)
In this study, the influence of process parameters on the behaviour of free radical homo-polymerization of styrene in a well mixed batch reactor was examined. The reaction of styrene with itself in hydrocarbon solvents of dissimilar polarities (acetone and chloroform) and non-hydrocarbon solvent (distilled and de-ionized water) was studied experimentally over ranges of solvent volumes, temperature, reaction time, and initiator type in a magnetically stirred thermo-well round bottom reactor. Similar reactions were carried out using equi-volumes of the solvent blend to explore the possibility of solvent synergy. This study uses the kinetic model of Coats-Redfern to evaluate kinetic parameters such as activation energy, order of reaction, and rate constant. This aspect becomes especially important as it is necessary to know in advance the parameters that will assist the occurrence of runaway reaction. The right choice of operating conditions of the styrene polymerization of known kinetics according to this study is a defense mechanism against runaway reaction. Although not discussed in this study, mischarging of reactants, maintenance troubles, agitator breakdown, etc. may also cause runaway reactions. Solution molecular weights of polystyrene samples were measured using the Mark-Houwink Sakurada equation and other procedures earlier reported. The gel effect and heat accumulation within the reactor system were less pronounced, giving a safety advantage to the solution/emulsion process compared to bulk. Further dilution of the monomer with the solvents effectively reduces the gel effects. Unlike in thermal polymerization process, the type of initiator and their mass concentration in the reacting mixtures reduce the reaction time, thereby minimizing the use of energy, making the process cost-effective.